THE EFFECT OF ORGANIZATIONAL SUPPORT ON EMPLOYEE ENGAGEMENT AND JOB SATISFACTION AND EMPLOYEE PERFORMANCE AT THE YOUTH AND SPORTS OFFICE IN EAST KUTAI REGENCY - Sitti Amina; Djoko Setyadi; Irwansyah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the influence of organizational support on employee engagement and job satisfaction and its impact on employee performance at the East Kutai Regency Youth and Sports Office. The method used is quantitative with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The research population is all employees in the agency with proportional sampling techniques. Data was collected through questionnaires and analyzed using SEM-PLS to test the relationships between variables. The results of the study show that organizational support has a positive and significant effect on employee engagement and job satisfaction. Employee engagement and job satisfaction also contribute positively and significantly to employee performance. In addition to organizational support, it directly affects the improvement of employee performance. These findings affirm the importance of the role of organizational support in creating a conducive work environment that increases engagement and job satisfaction which has an impact on improving performance. The recommendation of this study is to strengthen organizational support policies, such as improving work facilities, reward systems, and career development, to support optimal employee performance.